Religious moderation in the paradigm of religious conflict reconciliation in jayapura-papua - Athoillah Islamy; Amirullah (12 Waiheru, 2022)
This study intends to identify the values of religious moderation in the paradigm of inter-religious conflict reconciliation by FKUB Jayapura City. This qualitative research uses a normative-empirical-philosophical analysis approach. Primary data was taken through observation and interviews. The nature of this research approach is descriptive-analytic. The theory of analysis in this study is an indicator of religious moderation formulated by the Ministry of Religion of the Republic of Indonesia. Data analysis techniques include data reduction, data presentation, and data verification. The results showed that there were dimensions of religious moderation values in the conflict reconciliation paradigm implemented by the Religious Harmony Forum (FKUB) of Jayapura City. First, the values of anti-radicalism and tolerance in the socio-religious-based conflict reconciliation paradigm. This can be seen from the paradigm of inclusiveness of religious social values in the dialogue room which was attended by various interfaith leaders and community leaders. Second, the accommodative value of local wisdom and national commitment in the paradigm of conflict reconciliation based on culture and nationalism. This can be seen from the existence of space for religious and social aspirations in socio-cultural pluralism and the spirit of nationalism. The theoretical implication of this study shows that indicators of religious moderation in Indonesia can be a paradigm for fostering inter-religious harmony. The limitation of this research is that it has not examined what factors are the obstacles and supports the Jayapura City FKUB in efforts to reconcile conflicts between religious communities.